Fertility intentions and use of contraception among monogamous couples in northern Malawi in the context of HIV testing: a cross-sectional analysis. - Albert L N Dube; Angela Baschieri; John Cleland; Sian Floyd; Anna Molesworth; Fiona Parrott; Neil French; Judith R Glynn (PLoS ONE)
Context Knowledge of HIV status may influence fertility desires of married men and women. There is little knowledge about the importance of this influence among monogamously married couples and how knowledge of HIV status influences use of contraception among these couples. Methodology We carried out a cross-sectional analysis of interview data collected between October 2008 and September 2009 on men aged 15-59 years and women aged 15-49 years who formed 1766 monogamously married couples within the Karonga Prevention Study demographic surveillance study in northern Malawi. Results 5% of men and 4% of women knew that they were HIV positive at the time of interview and 81% of men and 89% of women knew that they were HIV negative. 73% of men and 83% of women who knew that they were HIV positive stated that they did not want more children, compared to 35% of men and 38% of women who knew they were HIV negative. Concordant HIV positive couples were more likely than concordant negative couples to desire to stop child bearing (odds ratio 11.5, 95%CI 4.3-30.7, after adjusting for other factors) but only slightly more likely to use contraceptives (adjusted odds ratio 1.5 (95%CI 0.8-3.3). Conclusion Knowledge of HIV positive status is associated with an increase in the reported desire to cease childbearing but there was limited evidence that this desire led to higher use of contraception. More efforts directed towards assisting HIV positive couples to access and use reproductive health services and limit HIV transmission among couples are recommended.